(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the influence of the Jadidism movement on the development of education of the Uzbek people, the contribution of the innovating teacher Abdulla Avloniy and other educators of this direction to the formation of Uzbek children’s literature.